Kedudukan Subsistem Kepolisian dalam Sistem Peradilan Pidana - Chairul Huda (Fakultas Hukum Universitas Islam Indonesia, 1999)
The sub system of police has been a control position in criminal justice system from where the effectiveness of the system has been determined. The refore, discourses on the position of the sub system of police has been alway sinteresting to do. Because the changes of function andres ponsibility of the sub system willgive agre at effecton the performance of the system as a whole, reposition of The Police of the Republic of Indonesia (POLR!) recently has to be supported by an andequate and academic responsible teoritical under standing.